2005
DOI: 10.1007/s10812-006-0020-5
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced defects in thin Cu(In,Ga)Se2 films on exposure to high-energy electron irradiation

Abstract: UDC 621.378At 4.2 K, the photoluminescence spectra of Cu(In,Ga)Se 2 films irradiated by electrons with an energy of 5 MeV displayed the 0.93-and 0.79-eV bands that owe their origin to the radiative recombination of nonequilibrium charge carriers on radiation-induced defects. The position of the energy levels of the defects is determined and their nature is discussed.Introduction. Creation of high-efficiency solar elements based on Cu(In,Ga)Se 2 (CIGS) is a topical scientifictechnical problem of contemporary se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Irradiation with MeV electrons, carried out at low temperatures, induces new bands in the PL spectra of such binary semiconductors as ZnSe [21], ZnO [22] and GaN [23]. MeV electrons also induce new bands in the PL spectra of CuInSe 2 [24] and Cu(In,Ga) Se 2 [25].…”
Section: Resultsmentioning
confidence: 99%
“…Irradiation with MeV electrons, carried out at low temperatures, induces new bands in the PL spectra of such binary semiconductors as ZnSe [21], ZnO [22] and GaN [23]. MeV electrons also induce new bands in the PL spectra of CuInSe 2 [24] and Cu(In,Ga) Se 2 [25].…”
Section: Resultsmentioning
confidence: 99%
“…As it is shown in Refs. [17,19], the defects in CIS films are related with In and Se vacancy or with the In substitution by Cu atoms that leads to the copper concentration increase. As a result of the films irradiation with the 40 keV Xe + ions (fluence 1 × 10 14 cm −2 ) a defect formation enhancement occurs with the copper concentration increase to 46 at.% (Table II).…”
Section: Figure 1 Presents the Rbs Hementioning
confidence: 99%
“…Besides, defect formation in this layer by both deposition and operation can result in degradation as well as solar elements efficiency rise [10][11][12][13][14][15][16][17][18][19]. This indicates insufficient investigation of defect creation in the CuInSe 2 films system and poor knowledge of these processes that does not allow to realize CIS potential in full.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments showed that the ratio of elements in the CIGS thin fi lms varied from Ga/(Ga + In) ~ 0.28 on the surface to ~0.58 near the glass substrate. It is noteworthy that heterogeneous distributions of In and Ga with a preferential increase of the Ga concentration near the glass substrate or a contact layer of Mo on glass were previously observed [7,[14][15][16]. This must be considered when analyzing the physical properties of CIGS solid solutions.…”
mentioning
confidence: 91%